1995
DOI: 10.1143/jjap.34.3351
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat-Treated 6H-SiC(0001) Surface Using Scanning Tunneling Microscopy

Abstract: A scanning tunneling microscopy in ultrahigh vacuum (UHV) has been used to study hexagonal (6H) silicon carbide (0001)Si face prepared by heat treatment. √3 ×√3, 6 ×6 and 3 ×3 reconstructions were observed above 1100°C. With increasing heat-treatment temperature, surface structure changed drastically and step heights decreased to that of a double layer. The 6 ×6 and 3 ×3 reconstructions can be explained as the structure of a graphite layer on the SiC surface and as the structure proposed by Kaplan, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…8 In view of this apparent importance of the surface structure for SiC growth, several investigations of its geometric structure and morphology have been carried out using low-energy electron diffraction (LEED) experiments [9][10][11] or scanning tunneling microscopy (STM). 10,[12][13][14][15][16][17] In our own earlier studies 10,12 of a 6H-SiC(0001) sample with STM we have found the surface morphology to be governed by step bunching into triple or multiples of triple steps. This is in complete accordance with our LEED structure analysis of the same surface 11 where we found only ABCACB stacking present on the surface.…”
Section: Sic Growth Polytypes and Surface Morphologymentioning
confidence: 99%
“…8 In view of this apparent importance of the surface structure for SiC growth, several investigations of its geometric structure and morphology have been carried out using low-energy electron diffraction (LEED) experiments [9][10][11] or scanning tunneling microscopy (STM). 10,[12][13][14][15][16][17] In our own earlier studies 10,12 of a 6H-SiC(0001) sample with STM we have found the surface morphology to be governed by step bunching into triple or multiples of triple steps. This is in complete accordance with our LEED structure analysis of the same surface 11 where we found only ABCACB stacking present on the surface.…”
Section: Sic Growth Polytypes and Surface Morphologymentioning
confidence: 99%
“…[7][8][9][10][11] As the latter still limits the performance of silicon carbide (SiC) in various nuclear radiation detection, 12 and high power, frequency, and temperature device applications, 13 the continued development of optimized SiC surface cleaning processes offers the potential to further the advancement of SiC for these applications. [21][22][23][24][25][26][27] However, these studies have largely ignored the presence of hydrogen, which is ubiquitous throughout semiconductor processing, 28 and has been shown in many cases to have a profound effect on surface/interface reactivity [29][30][31][32][33] and device performance. [18][19][20] In this regard, numerous studies related to SiC surface cleaning and preparation have been reported and have focused primarily on carbon, oxygen, and fluorine related contamination species.…”
Section: Introductionmentioning
confidence: 99%
“…The hexagonal bilayer of SiC, i.e., the ͑0001͒ plane in hexagonal and the ͑111͒ plane in cubic polytypes, is of particular importance in that respect as it is the most widely used growth plane. A number of investigations dealing with the properties of surfaces in these orientations have recently been reported whereby most of the publications [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] deal with qualitative aspects such as stoichiometry and surface preparation. Little experimental work, however, has been published concerning the electronic band structure of SiC.…”
Section: Introductionmentioning
confidence: 99%